Effect of Boxing Exercises on the Functional Ability and Quality of Life of Individuals with Parkinson's Disease: A Systematic Review - Nikolaos Chrysagis; Georgia Trompouki; Dimitris Petropaulis; George A. Koumantakis; Georgios Krekoukias; Georgios Theotokatos; Emmanouil Skordilis; Vasiliki Sakellari (MDPI AG, 2024)
Parkinson's disease (PD) is a neurological disorder caused by the loss of dopamine-producing cells in the substantia nigra and characterized by motor and non-motor symptoms. Boxing is a type of complementary therapy to improve symptoms in PD. The purpose of the present study was to examine the effect of boxing training on the functionality and quality of life of patients with PD. The literature search was performed on PubMed, Scopus, PEDro, Cochrane Library, and Google Scholar search engines. The PEDro scale was used to assess the methodological quality of the studies. This systematic review included three studies that examined disease severity, mobility, physical activity, balance, and quality of life. According to the PEDro scale criteria, the three articles included were of high methodological quality. Statistically significant improvements after the implementation of boxing training was shown for balance and quality of life in contrast to the other variables. Boxing training intervention programs had a positive effect on balance and quality of life in patients with PD; however, the results are conflicting regarding certain functionality variables. Therefore, it is necessary to conduct further research to examine the effectiveness of boxing training on the functionality and quality of life of patients with Parkinson's disease.